Energy security of the country: case for Ukraine and EU - Lyulyov, Oleksii; Pimonenko, Tetyana (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional Development, 2022)
The core goal Green Deal Policy is providing energy security for countries’ green growth. Moreover, the ongoing political crisis and countries’ energy dependence necessitate the development of effective instruments for providing energy security. The paper aimed to estimate the countries’ energy security to identify energy security’s core drivers and bottlenecks in the EU and Ukraine. The study contained two main stages: 1) bibliometric analysis – to identify the scientific background on the abovementioned issues and develop the theoretical framework of the investigation; 2) to estimate the energy security of the country. The findings of bibliometric analysis (co-occurrence criteria) confirmed the growth of the papers’ number, which focused on the investigation of energy security. Thus, the papers’ number has increased 2.5 times over the past five years. The results allowed to identify the three core triggers that affect energy security: environmental (greenhouse gas emissions, environmental quality, etc.), institutional (efficiency of public administration, infrastructure development, etc.) and behavioural (society willingness to adopt energy and resource-saving lifestyles, considering environmental factors in decision-making, etc.). The objects of the investigation are the EU countries and Ukraine (as the potential EU member). The data for the years 2000-2020 were obtained from Eurostat, World Data Bank, Ukrstat, OECD. The study applied the method based on the MARKAL model to estimate the energy security of the countries, as well as Godric-Prescott and Butterworth filters to consider the indicators’ fluctuation of energy security. The findings concluded that Ukraine (as the potential EU member) should converge with EU policies in the energy sector to increase energy security. Moreover, Ukraine should adopt EU practices to extend green energy technologies, promote a green mind and lifestyle among society, and create supporting instruments for developing alternative energy.